Bentuk Internalisasi Nilai Etik Mengenai Bias Negatif dan Diskriminasi Dalam Platform generative AI (RechtJiva, 2024)
This research discusses a form of classification in the realm of Artificial Intelligence, namely generative AI. Generative AI is an AI technology that can create new content in the form of text, images, audio, and others. However, generative AI has the potential to cause problems such as negative bias and unintentional discrimination in the form of negative stereotyping of a racial group. Current regulations are inadequate to address these challenges and determine the liability of parties in the event of harm. This research aims to analyze the urgency of new regulations related to generative AI for anti-bias and discrimination. The approach is normative juridical using statutory, conceptual, and comparative approaches. The results show that current regulations do not adequately protect the public from bias and discrimination by AI. New regulations are needed that include AI ethical principles, AI audits, classification of parties' responsibilities (developers, data providers, regulators), and application of the principle of liability based on fault. These regulations are important to ensure responsible use of generative AI and respect for human rights. In conclusion, current regulations need to be refined and new ones created to address the ethical and liability challenges in the utilization of generative AI in line with anti-discrimination principles.